Superdiversity and conviviality: exploring frameworks for doing ethnography in Southern European intercultural cities - Padilla, B.; Azevedo, J.; Olmos-Alcaraz, A. (Ethnic and Racial Studies, 2015)
International migration contributes to increasing cultural diversity in many European cities. Historically, migration studies have focused on the integration of immigrants foregrounding race/ethnicity and identity issues, limiting our understanding of intercultural diversity. A new paradigm focusing on relational patterns among groups is emerging, highlighting the importance of mutual relations, interactions and influences among residents of different origins and backgrounds, including the experience of both immigrants and autochthonous populations. The notions of superdiversity and conviviality have significantly contributed to this debate. This paper discusses how both were methodologically operationalized in multi-sited ethnographies carried out in Lisbon and Granada, during 2009–2012. Superdiversity and conviviality are the main theoretical frameworks used to understand how interculturality is lived and experienced at the local level. We reflect on their strengths and weaknesses, unpacking common assumptions about race, ethnicity and culture, specifically looking at the negotiation of difference in intercultural events.